Stroke Recovery in Rats after 24‐Hour–Delayed Intramuscular Neurotrophin‐3 Infusion. Issue 1 (28th December 2018) - Duricki, Denise A.; Drndarski, Svetlana; Bernanos, Michel; Wood, Tobias; Bosch, Karen; Chen, Qin; Shine, H. David; Simmons, Camilla; Williams, Steven C. R.; McMahon, Stephen B.; Begley, David J.; Cash, Diana; et al.
Abstract : Objective: Neurotrophin‐3 (NT3) plays a key role in the development and function of locomotor circuits including descending serotonergic and corticospinal tract axons and afferents from muscle and skin. We have previously shown that gene therapy delivery of human NT3 into affected forelimb muscles improves sensorimotor recovery after stroke in adult and elderly rats. Here, to move toward the clinic, we tested the hypothesis that intramuscular infusion of NT3 protein could improve sensorimotor recovery after stroke. Methods: Rats received unilateral ischemic stroke in sensorimotor cortex. To simulate a clinically feasible time to treatment, 24 hours later rats were randomized to receive NT3 or vehicle by infusion into affected triceps brachii for 4 weeks using implanted catheters and minipumps. Results: Radiolabeled NT3 crossed from the bloodstream into the brain and spinal cord in rodents with or without strokes. NT3 increased the accuracy of forelimb placement during walking on a horizontal ladder and increased use of the affected arm for lateral support during rearing. NT3 also reversed sensory impairment of the affected wrist. Functional magnetic resonance imaging during stimulation of the affected wrist showed spontaneous recovery of peri‐infarct blood oxygenation level–dependent signal that NT3 did not further enhance. Rather, NT3 induced neuroplasticity of the spared corticospinal and serotonergic pathways. Interpretation: Our results show that delayed, peripheral infusion of NT3 can improve sensorimotor function after ischemic stroke. Phase I and II clinical trials of NT3 (for constipation and neuropathy) have shown that peripheral high doses are safe and well tolerated, which paves the way for NT3 as a therapy for stroke.ANN NEUROL 2019;85:32–46.